Review: The Sermons of Charles Wesley. A Critical Edition with Introduction and Notes - Macquiban, Tim (The journal of theological studies, 2002)
The Sermons of Charles Wesley. A Critical Edition with Introduction and Notes Kenneth G. C. Newport xi + 407 Oxford University Press 2001 £70 0 19 826949 8